Pengawasan Internal Dalam Meningkatkan Disiplin Kerja Pegawai Negeri Sipil di Dinas Pekerjaan Umum Sumber Daya Air Kabupaten Bojonegoro - Safira, Farrah Della; Rupiarsieh; Prasetijo, Kusnandaka Tjatur (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
Internal control is a policy of specification procedures designed to provide adequate confidence for management that the goals and objectives important to the company's management can be met. The Bojonegoro Regency Water Resources Public Works Office is an element that implements local government affairs in the field of public works in the water resources sub- affairs. There are several problems that often occur in the Water Resources Public Works Office (DPUSDA) related to employee discipline, namely the main problem that arises is the frequent entry of employees of the Water Resources Public Works Office (DPUSDA) into the office outside of the set working hours. Some employees were even seen returning to the office after breaks without adhering to the predetermined schedule. The research method used in this study is qualitative descriptive, with the focus of the research being based on Presidential Regulation of the Republic of Indonesia Number 116 of 2022 concerning Supervision and Control of the Implementation of Norms, Standards, Procedures, and Criteria for the Management of the State Civil Apparatus. This study provides the results of the Implementation of NSPK ASN Management: The Implementation of Norms, Standards, Procedures, and Criteria (NSPK) at the Water Resources Public Works Office (PU SDA) of Bojonegoro Regency has improved the discipline of Civil Servants (PNS). Although the majority of employees comply with the rules of working hours, there are still some employees who are absent when returning home due to duties outside the office. Technical Guidance: The training provided by the Bojonegoro Regency Personnel, Education, and Training Agency (BKPP) focuses on improving the competence and professionalism of ASN. Individual and team consultations at the Public Works and Natural Resources Office have played an important role in improving work discipline. Specific assessments and support through individual consultations. Monitoring and Evaluation: The use of fingerprint attendance and the SiKepo application has improved the discipline and accuracy of employee attendance recording. While there are some challenges in meeting targets, continuous evaluation helps identify and improve performance that is not optimal. Utilization of Information Systems: The use of electronic attendance systems and the SiKepo application has increased transparency, accountability, and employee attendance management. The results of the analysis show that the discipline is quite good, but further improvement is still needed to achieve more effective human resource management